Can deep eutectic solvents be used to mobilise copper from tailings while providing a pathway towards rehabilitation? - De Oliveira, VH; Duddigan, S; Symons, J; Whelan, MJ; Selvaraj, V; Abbott, AP; Jenkin, GRT; Tibbett, M (Mine Closure 2024: Proceedings of the 17th International Conference on Mine Closure, 2024)
The use of deep eutectic solvents (DESs) has been proposed as a novel technique for environmentally benign mineral processing, with utility in the reprocessing of legacy tailings in a process known as solvometallurgy. These solvents can leach a wide range of metals while having many advantages, such as low volatility, high target metal selectivity, lower production costs and potentially low ecotoxicity. We aimed to determine the capacity of different DESs to mobilise copper (Cu) and other metals from Cu mine tailings. They were: DES 1 (oxaline) – choline chloride + oxalic acid; DES 2 (ethaline) – choline chloride + ethylene glycol; DES 3 – betaine + acetic acid; and DES 4 – betaine + acetic acid + phosphoric acid. In a follow-up experiment, Plantago lanceolata seedlings were transplanted to the tailings after DES application in order to determine phytotoxic responses. Our results showed that Cu extraction from tailings increases with DES concentration and pointed to DES 3 and 4 (betaine-based) as more efficient in Cu leaching, although oxaline was more capable of enhancing nutrient availability. Almost all plants died 24 hours after transplanting to DES-treated tailings, except the ones treated with oxaline, which is possibly linked to the remarkable macronutrient mobilisation – an element known to alleviate Cu phytotoxicity. However, only the diluted oxaline (1:128, DES:water) was able to improve plant growth in tailings as it mobilised more nutrients, leading to greater plant biomass and chlorophyll content. Thus it is clear that hazardous effects will depend on the DES formulation, concentration and exposure route, which may promote extreme phytotoxicity by enhancing metal availability in mine tailings. Yet diluted oxaline showed promising beneficial effects in plant health and growth, indicating that some diluted DESs, at concentrations anticipated after application and leaching, may have a role in promoting land rehabilitation.
Keywords: DES